Inside Back Cover: Simulating Spatial Microwave Manipulation of Polyatomic Asymmetric‐Top Molecules Using a Multi‐Level Approach (ChemPhysChem 22/2016). Issue 22 (17th November 2016) - Graneek, Jack B.; Merz, Simon; Patterson, David; Betz, Thomas; Schnell, Melanie
Abstract : The Inside Back Cover describes the AC‐Stark effect on a multi‐level molecular system, 4‐aminobenzonitrile (4‐ABN). The proposed experimental set‐up utilizes the AC‐Stark effect to manipulate the motion of a molecular packet of 4‐ABN with a tailored resonance mode of a microwave resonator. More information can be found in the Full Paper by M. Schnell and co‐workers on page 3624 in Issue 22, 2016 (DOI: 10.1002/cphc.201600538 ).